An Assessment of the Determinants of University Technology Transfer. (February 2013) - González-Pernía, José L.; Kuechle, Graciela; Peña-Legazkue, Iñaki
We study the extent to which the characteristics of universities and technology transfer offices located within different regional contexts affect the transfer of scientific knowledge, both in the form of licensing and spin-off firm creation. By using data from Spain for the period 2005 to 2008, we show that technology transfer offices with more experienced and expert staff teams and universities with clearly established rules for creating academic startups and with higher patenting records are more likely to obtain better university technology transfer results (i.e., licensing and spin-off firm outcomes). Although the effects of R&D investment and venture capital available in the local region were not significant, the (subnational) regional context seemed to matter for explaining the variation in academic spin-off and licensing outcomes across universities.